2012
DOI: 10.1126/science.1214935
|View full text |Cite
|
Sign up to set email alerts
|

Disease Tolerance as a Defense Strategy

Abstract: The immune system protects from infections primarily by detecting and eliminating the invading pathogens; however, the host organism can also protect itself from infectious diseases by reducing the negative impact of infections on host fitness. This ability to tolerate a pathogen’s presence is a distinct host defense strategy, which has been largely overlooked in animal and human studies. Introduction of the notion of “disease tolerance” into the conceptual toolkit of immunology will expand our understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
1,440
0
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,437 publications
(1,570 citation statements)
references
References 57 publications
32
1,440
0
17
Order By: Relevance
“…This is coupled to the induction of cellular and tissue regenerative responses that restore the functional output of damaged parenchyma tissues 3,23 . As discussed in further detail below, different types of infection impose distinct forms of stress and damage to host parenchyma cells, suggesting that tissue damage control mechanisms 3 might act in a somewhat pathogen class-specific manner that reflects these differences such as to effectively establish disease tolerance against diverse types of infection 6 . While there are clearly parallels between the protective effect exerted by tissue damage control mechanisms in the context of infectious and non-infectious diseases 1, 6, 24 , we shall restrict our discussion here to infectious diseases.…”
Section: Tissue Damage Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…This is coupled to the induction of cellular and tissue regenerative responses that restore the functional output of damaged parenchyma tissues 3,23 . As discussed in further detail below, different types of infection impose distinct forms of stress and damage to host parenchyma cells, suggesting that tissue damage control mechanisms 3 might act in a somewhat pathogen class-specific manner that reflects these differences such as to effectively establish disease tolerance against diverse types of infection 6 . While there are clearly parallels between the protective effect exerted by tissue damage control mechanisms in the context of infectious and non-infectious diseases 1, 6, 24 , we shall restrict our discussion here to infectious diseases.…”
Section: Tissue Damage Controlmentioning
confidence: 99%
“…However, the trade-off of this resistance mechanism can be particularly high, depending on the relative capacity of different tissues to withstand cell loss without compromising tissue function and homeostasis 6 . The pathophysiological relevance of this defense strategy is supported by the number of mechanisms deployed by intracellular pathogens to promote or inhibit host genetic programs controlling programmed cell death, presumably as a strategy to escape resistance to infection 70 .…”
Section: Programmed Cell Death In Tissue Damage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease tolerance is a defense strategy that reduces the negative impacts of the infection on host fitness without reducing the parasite load. The term employed here is different to immunological tolerance (i.e., the process by which the immune system fails to attack an antigen), but rather captures the idea that the costs of the infection can be reduced through reducing the damage caused by the infection and activation of the immune system on host tissues (Ayres and Schneider, 2012;Medzhitov et al, 2012). For example, Ayres and Schneider, (2009) found that during Salmonella infections, food-restricted Drosophila and flies mutant for the gustatory receptor, gr28b, had similar levels of bacteria to wild-type individuals but they lived longer.…”
Section: Nutrition and The Consequences Of Immune Trade-offsmentioning
confidence: 99%
“…Alternatively the dissemination of infection may result in tissue damage because bacteria express virulence factors with deleterious cell effects (e.g., alterations in homeostasis of endoplasmic reticulum or mitochondria; impairment of the induction of tissue repair program) [21]. Future studies should address these points.…”
mentioning
confidence: 99%